Fragmentation dynamics of liquid–metal droplets under ultra-short laser pulses. (17th January 2017) - Basko, M M; Krivokorytov, M S; Yu Vinokhodov, A; Sidelnikov, Yu V; Krivtsun, V M; Medvedev, V V; Kim, D A; Kompanets, V O; Lash, A A; Koshelev, K N
Abstract: We present the measurements and theoretical analysis of the deformation and fragmentation of spherical liquid–metal drops by picosecond and subpicosecond laser pulses. In the experiments, 60 μ m droplets of Sn–In alloy were irradiated by Ti:Sa laser pulses with a peak energy fluence of  ̃100 J cm −2 . The observed evolution of the droplet shape dramatically differs from that previously reported for nanosecond pulses. Invoking 2D hydrodynamic simulations, we explain how, due to the specifics of matter dynamics in the liquid–vapor phase coexistence region, a liquid droplet is transformed into a characteristic acorn-like expanding shell with two inner cavities. High sensitivity of the measured shell parameters to the details of the equation of state and metastable dynamics suggests that such experiments offer new possibilities in exploration of thermophysical properties of metals in the region of liquid–vapor phase transition.